Tingkat Kebangkrutan Dan Karakteristik Perusahaan Terhadap Nilai Perusahaan (Sebuah Model : Pendekatan Springate) - Tri Astuti (JRB-Jurnal Riset Bisnis, 2018)
This study aims to examine the effect of Z-Score, Size Firm, Leverage Ratio, Sales Growth on the Value of the Company proxied as PBV, studies in Telecommunications Companies listed in the Indonesia Stock Exchange. The data used in this study was obtained from the Telecommunication Sector Publication Financial Report for the period 2010-2016. The data analysis model used was multiple linear regression with the least squares equation. The results of this study indicate that Z’Score has no significant effect on PBV, Variable Size has a significant positive effect on PBV, Leverage has a positive effect on PBV and Growth has no significant effect on PBV. Variable Z-Score (Z), Size Firm (Size), Leverage Ratio (Leverage), Sales Growth (Growth) simultaneously simultaneously affect the dependent variable Corporate Value (PBV). Test of determination or variation of the models of the four variables on PBV in this study amounted to 90.2% while the remaining 9.8% was influenced by other variables not included in the company model.